On Housing-Related Financial Fears of Baby Boomer Women Living Alone in Switzerland - Yashka Huggenberger; Antonin Beringhs; Joël Wagner; Gabrielle Wanzenried (Social Sciences, 2025)
The ageing population and rising housing costs in Switzerland are increasing the number of older adults facing financial housing concerns. Older women have particularly limited housing choices because they, on average, earn less, live longer, and are more likely to live alone. This study explores potential levers to alleviate housing-related financial fears among baby boomer women (aged 55–75) living alone in Switzerland, a subject with limited academic coverage. Using regression and random forest models on unique 2023 survey data (<semantics>N=371</semantics>), we examine the influence of socio-demographic, financial, well-being, and housing factors on fears related to affordability, price increases, and lack of housing supply. Key findings show that ownership status, perceived financial situation, and concerns about maintaining one’s lifestyle significantly drive these fears. The fear of unsuitable housing strongly influences perceived lack of supply. These results highlight the importance of retirement planning and support the consideration of measures such as reverse mortgages, co-housing, subsidies, and rent-controlled units.